Republic of Belarus : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Belarus authorities are moving in the direction of a flexible exchange rate system supported by an inflation-targeting (IT) regime, which would have significant benefits for the economy. A full-fledged IT framework (FFIT) requires a number of essential building blocks, which could be viewed as components of sound macroeconomic management. There are three additional features that could interfere with the IT regime. Some of the building blocks are essentially prerequisites for a successful launch of the IT regime; others could be developed (or fine-tuned) during early stages of IT implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet